PENGARUH KARAKTERISTIK INDIVIDU, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PADA AMPINDO ( AKADEMI MANAJEMEN PERPAJAKAN INDONESIA ) BLITAR - Nunuk Latifah (Universitas Islam Kadiri, 2020)
Diploma) in Blitar. To produce students who are experts in the field of Banking and Finance and Taxation Management not only of teachers who have a good competence, but must be supported by good organizational management. In the management of this organization consists of faculty and employees. Phenomenon that researchers take notice of the acceptance of teachers and employees or recruitment in Blitar AMPINDO which tend not selective for the prospective teachers and employees who will be placed, it is seen from the educational background of prospective teachers and employees who are not in accordance with job placement given by AMPINDO Blitar so that the impact on the ability, skills and interests to support the advancement of Blitar AMPINDO tend to be less. So based on the background of the discussion, the purpose of this study is: To determine the effect of individual characteristics variables simultaneously, motivation and job satisfaction on performance variables. To determine the effect of partial variable individual characteristics, motivation and job satisfaction on performance variables. To determine which variable among individual characteristics, motivation and job satisfaction of the most dominant effect on performance. In this study the entire population sampled, or so-called saturation sampling so that the sample in this study as many as 57 people, to support this study used two types of data, namely primary data taken directly from the source / respondent / target observation. Secondary data is data that is sourced from a variety of documents / records are deliberately kept as material analysis, which is around the respondents.